The antibacterial performance of a residual disinfectant against Staphylococcus aureus on environmental surfaces - Omardien, Soraya; Pingulkar, Sarvesh; Thayagan, Mariska; Buniotto, Laura; de Oliveira Negreiros, Mateus (Frontiers in Microbiology, 2024)
Environmental surfaces play a key role in transmitting pathogens that can survive on surfaces for long durations. The interest in long-lasting or residual disinfectants are, therefore, growing as it might protect surfaces for longer than traditional disinfectants. In this study, a quat-based product claiming residual disinfecting performance against bacteria, among other microorganisms, was tested using an approved standardized method, in a controlled laboratory study and on environmental surfaces in an office building. The results obtained showed that the residual disinfectant can reduce the bacterial counts significantly compared to a traditional quat-based disinfectant when used on horizontal surfaces, twenty-four hours after application. During the standardized test method, the residual disinfectant provided a 6-log reduction, whereas the traditional disinfectant provided only a 1.9-log reduction. Similarly, the residual disinfectant provided a 2.5 log reduction in the laboratory study, whereas the traditional disinfectant had too-numerous-to-count colonies. When tested on environmental surfaces, an ANOVA statistical analysis indicated that surfaces treated with the residual disinfectant had significantly less bacteria present twenty-four hours after application. The antibacterial performance of the residual disinfectant showed to be limited by the orientation of the treated surface, and the thickness of the product film dried on the surface. This study showed the potential of residual disinfectants that warrants further investigation and could potentially aid the further development of the technology.